2006
DOI: 10.1002/cncr.21924
|View full text |Cite
|
Sign up to set email alerts
|

Trends in distribution and prognostic significance of Gleason grades on radical retropubic prostatectomy specimens between 1989 and 2001

Abstract: BACKGROUNDThe objectives of the current study were to examine time trends in the prevalence of Gleason grades of prostate cancer on radical retropubic prostatectomy (RRP) specimens and to assess the resultant impact on prognosis.METHODSThe authors examined the prevalence over time of each grade and Gleason score (GS) on RRP specimens from 8750 patients who were treated between 1989 and 2001. Biochemical recurrence‐free survival (BRFS), which was estimated by using Kaplan–Meier methodology, was examined in subg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
1
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 25 publications
(43 reference statements)
0
21
1
3
Order By: Relevance
“…The comparisons between the results of the histological biopsy compared to the surgical specimen exhibited a correlation equal to ~50% (14)(15)(16)(17). The results of the prostate biopsy and the surgical specimen may differ for several reasons, such as incorrect evaluation by the pathologist, sampling errors and the presence of borderline grading.…”
Section: Discussionmentioning
confidence: 99%
“…The comparisons between the results of the histological biopsy compared to the surgical specimen exhibited a correlation equal to ~50% (14)(15)(16)(17). The results of the prostate biopsy and the surgical specimen may differ for several reasons, such as incorrect evaluation by the pathologist, sampling errors and the presence of borderline grading.…”
Section: Discussionmentioning
confidence: 99%
“…9 Furthermore, changes by pathologists in the interpretation of prostate biopsies have had a significant effect on the grade migration of prostate cancer. 7,10,11 If changing practice patterns can contribute to a grade migration of prostate cancer, then it is likely that these changes have had other influences as well. With this in mind, we hypothesized that the correlation between PSA and positive biopsy rate could have been altered by changes in prostate biopsy practice patterns.…”
mentioning
confidence: 99%
“…25 These trends have been attributed to changes in the approach to diagnosis of prostate cancer, an increase in expertise among pathologists, and redefinition of some of the criteria on which the scoring system is based. 21,26 As would be expected based on the differences between scoring systems, concordance between reviews was greatest at lower grades. Above score 6, interobserver variability is likely to have a greater role because the individual contributions of pattern 3 and pattern 4 are crucial in determining whether a tumor is grade 6 or 7.…”
Section: Commentmentioning
confidence: 57%
“…20 One study 21 confirmed a progressive increase in Gleason 3 and a decrease in Gleason 2 on radical retropubic prostatectomy specimens over time (1989)(1990)(1991)(1992)(1993)(1994)(1995)(1996)(1997)(1998)(1999)(2000)(2001), and other studies [22][23][24][25] have reported a decrease in the proportion of Gleason tumors scored 2 to 5 and an increase in Gleason 6 and 7 tumors. Correlation of Gleason score between biopsy and radical prostatectomy has been shown to increase over time, from 58% in 1992-1996 to 75% in [2002][2003][2004][2005][2006].…”
Section: Commentmentioning
confidence: 99%